2017
DOI: 10.1016/j.jvs.2016.08.099
|View full text |Cite
|
Sign up to set email alerts
|

Immediate changes of angiosome perfusion during tibial angioplasty

Abstract: There is a significant overall improvement in tissue perfusion of the foot immediately after tibial angioplasty. The effect shown in this study, however, was found to be global and was not restricted to certain borders, such as defined by angiosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 32 publications
1
28
1
2
Order By: Relevance
“…Similar results have already been reported when measuring the immediate changes of tissue perfusion after tibial angioplasty; in these previous studies, the impact of tibial angioplasty on the foot's skin microcirculation was investigated by laser doppler flowmetry and white light tissue spectrometry, with an overall improvement of the foot perfusion identified, but no difference recognised in directly and indirectly revascularised angiosomes. 15 Interestingly, in the present study, in a subgroup analysis of diabetic patients, the microcirculatory improvement in the directly revascularised angiosomes was elevated in comparison with the indirectly revascularised angiosomes. However, this finding in a small subgroup of 16 patients must be interpreted with caution and requires further evaluation in future larger cohorts, as the impact of the angiosome concept in diabetic patients is debatable.…”
Section: Discussioncontrasting
confidence: 43%
“…Similar results have already been reported when measuring the immediate changes of tissue perfusion after tibial angioplasty; in these previous studies, the impact of tibial angioplasty on the foot's skin microcirculation was investigated by laser doppler flowmetry and white light tissue spectrometry, with an overall improvement of the foot perfusion identified, but no difference recognised in directly and indirectly revascularised angiosomes. 15 Interestingly, in the present study, in a subgroup analysis of diabetic patients, the microcirculatory improvement in the directly revascularised angiosomes was elevated in comparison with the indirectly revascularised angiosomes. However, this finding in a small subgroup of 16 patients must be interpreted with caution and requires further evaluation in future larger cohorts, as the impact of the angiosome concept in diabetic patients is debatable.…”
Section: Discussioncontrasting
confidence: 43%
“…This technique is also used for periprocedural perfusion measurements in the foot following balloon angioplasty. Measuring perfusion in the foot angiosome following isolated crural measurement showed that there was no significant difference between direct and indirect revascularization on the microcirculatory level: on the contrary, an improvement in overall foot perfusion was seen following revascularization [13, 14].
Fig.
…”
Section: Oxygen-to-see (O2c) Methodsmentioning
confidence: 99%
“…True clinical application of the AC primarily implies thorough evaluation of the benefit allowed by targeted macroand microvasculature reperfusion [17] [27]. Effective flow mapping toward the wound zone ( Figure 1) [20] already revealed the clinical importance of foot arches in topographic reperfusion, while Osawa [19], Zheng [18], and Acin [55] [22]. The importance of the notion "mean-time to tissue recovery" appears then to be ponderous in defining real benefits of DR/WTR versus IR [17] [55].…”
Section: The Relevance Of Wtr In Current Vascular Practicementioning
confidence: 99%
“…A few contemporary studies add the WTR notion to DR, or to "DR-collateral enhanced" according to the AC [3] [10] [18] [19] as primary intention to treat CLTI. These studies reveal several observational advantages of this theory [10] [17] [18] [19] and obviously, some inherent uncertainties [20] [21] [22] [23].…”
Section: Introductionmentioning
confidence: 99%